IMPROVEMENT OF APPROACHES TO THE FORMATION OF A QUALITY MANAGEMENT SYSTEM AT A PHARMACEUTICAL ENTERPRISE - Рєпіна, Інна М. (Journal of Strategic Economic Research, 2023)
The world market of the pharmaceutical industry is highly competitive and dynamically developing, therefore the value of requirements for the organization of management of pharmaceutical enterprises is more significant today. In these conditions, the implementation of a quality management system that meets the requirements of ISO 9001:2015, its integration with other management systems is an important strategic task for the management of a pharmaceutical enterprise. The purpose of the study is the further development of methodological, methodical and practical approaches to the formation, improvement and implementation of the quality management system at the pharmaceutical industry enterprises, which meets the requirements of ISO 9001:2015, and the analysis of the possibilities and advantages of its integration with other management systems at the enterprise. The research used scientific research methods, such as theoretical generalization, analysis, synthesis, induction, deduction. The article examines the main methodological and methodological provisions of the formation and certification of the quality management system that meets the requirements of ISO 9001:2015, and analyzes the possibilities of its integration with other management systems at the pharmaceutical industry enterprise. The main stages of the formation of the quality management system are the development of quality management system documentation and the implementation of measures to bring the company’s activities into compliance with the requirements of ISO 9001:2015, certification. Currently, integrated management systems that meet the requirements of two or more international standards have become widespread. But the basis for integration is always the ISO 9001 standard, so the quality management system must be carefully designed and effective. For pharmaceutical enterprises, the integration of a quality management system that meets the requirements of ISO 9001 with management systems that meet the requirements of GMP, ISO 14001, ISO 45001, etc. standards is most common. The development and implementation of a quality management system that meets the requirements of ISO 9001:2015, its integration with other management systems is a strategic decision of the management of the pharmaceutical enterprise, which provides opportunities to ensure the quality and safety of medicinal products, economical use of resources; reduction of financial costs associated with the production of low-quality medicinal products; ensuring optimal operation of quality control systems; increasing consumer confidence in the safety and quality of medicinal products; expanding sales markets and entering new markets; attraction of investors; ensuring the reputation of the manufacturer of high-quality and safe medicines of the pharmaceutical industry.